Informal coercion as a neglected form of communication in psychiatric settings in Germany and Switzerland. (April 2018) - Elmer, Timon; Rabenschlag, Franziska; Schori, Dominik; Zuaboni, Gianfranco; Kozel, Bernd; Jaeger, Susanne; Mahlke, Candelaria; Heumann, Kolja; Theodoridou, Anastasia; Jaeger, Matthias
Abstract: Aims: Informal coercion is a frequently used form of communication among mental health professionals to influence treatment outcomes. This study investigates the recognition, attitude, and application of different forms of informal coercion by mental health professionals. Methods: Mental health professionals of five psychiatric institutions in Germany and Switzerland ( n = 424 ) took part in an online survey assessing the recognition of, attitudes towards, and application of different forms of informal coercion. Results: Mental health professionals did not recognize the extent of informal coercion adequately; especially stronger forms were underestimated. Recognition and application of informal coercion was predicted by attitudes towards coercion. Furthermore, there were differences between profession of participants regarding the recognition and application of informal coercion. Conclusions: It is important to realize that the extent of applied informal coercion in therapeutic communication is often not recognized by practitioners, although it might interfere with a sound therapeutic relationship. Highlights: Threat as a strong form of informal coercion as well formal coercion was more underestimated by psychiatric health professionals than persuasion and leverage as weaker forms of informal coercion. Health professionals with a positive attitude towards persuasion, leverage, and threat tended to underestimate the coercion level significantly more than participants disapproving those practices. No significant relationships were found between recognition, attitude and application of informal coercion and social distance, ward atmosphere, and distress symptoms.